1986
DOI: 10.1002/1097-0142(19860401)57:7<1302::aid-cncr2820570709>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma. Inflammatory mononuclear cell infiltrates in cerebral metastases during concurrent therapy with viral oncolysate

Abstract: Five patients with advanced malignant melanoma, treated with viral oncolysate, had solitary central nervous system metastases that were removed surgically. Histologic examination revealed striking and significant mononuclear inflammatory cell infiltrates, consisting of a mean of 60% plasma cells and a lesser proportion of lymphocytes at the edges of the lesions, within their supporting fibrovascular trabeculae, and among the tumor cells. Comparable inflammatory changes were not found in solitary metastatic mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…18 -22 The CNS, however, is considered to be an immunologically privileged site where a systemic immune response fails to prevent tumor growth. [3][4][5][6][7] Sampson et al 11 reported that s.c. vaccination with irradiated, cytokine-producing tumor cells was effective for the treatment of brain tumors, but complete elimination of brain tumors was seldom achieved by this strategy. We have shown that s.c. inoculation of 9L/IL-2 cells suppressed the growth of i.c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 -22 The CNS, however, is considered to be an immunologically privileged site where a systemic immune response fails to prevent tumor growth. [3][4][5][6][7] Sampson et al 11 reported that s.c. vaccination with irradiated, cytokine-producing tumor cells was effective for the treatment of brain tumors, but complete elimination of brain tumors was seldom achieved by this strategy. We have shown that s.c. inoculation of 9L/IL-2 cells suppressed the growth of i.c.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Impaired immunological reactions in the brain were also evidenced by other studies in experimental and clinical immunotherapies for brain tumors. [5][6][7] Recent studies, however, showed that cytokines such as interleukin-2 (IL-2), IL-4, or granulocyte-macrophage colony-stimulating factor secreted from tumor cells could suppress the growth of inoculated brain tumors, although complete elimination of the tumors was rarely observed. 8 -13 An immune response within the CNS may be different from that in other organs, but these studies indicate that the CNS is possibly subjected to cytokine-assisted immunogene therapy.…”
mentioning
confidence: 99%
“…7,11 In addition, tumors established within the CNS have failed to respond to other forms of systemic immunotherapy. [27][28][29][30] The CNS may pose a barrier to using cytokinesecreting tumor vaccine. However, according to recent evidence, the immunity elicited by the subcutaneous injection of cytokine-secreting tumor vaccines can regress tumors implanted in the brain, suggesting that the immunologically privileged CNS is not an absolute barrier to this form of active, specific immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The CNS, however, has been shown to be a barrier to allograft and xenograft rejection and has been considered an "immunologically privileged" site both historically (16,17) and more recently (18). Indeed, the concept that immunologic reactions against tumors within the CNS may be impaired has been supported by other studies of experimental (19) and clinical (20)(21)(22) immunotherapies where systemic responses failed to prevent tumor growth in the CNS. The CNS, then, may pose a significant barrier to the use of cytokine-assisted tumor vaccines.…”
mentioning
confidence: 99%